Analisis Stabilitas Spillway Embung Lakuang Burai Kabupaten Limapuluh Kota - Dent Siloana; Siswanto Siswanto; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Lakuang Burai Small dam is a permanent reservoir built in 2019 which is located in Kenagarian Taeh Bukit, Payakumbuh District, Limapuluh Kota Regency. In the dry season there is a lack of water reserves in Kenagarian Taeh Bukit. Seeing this problem, the central government built a reservoir that is expected to be able to accommodate water reserves during the rainy season and can be used during the dry season.The initial steps undertaken in this analysis are hydrological analysis, determination of rainfall, analysis of rainfall in Log Person Type III method, calculation of design flood for 50-year return period using rational methods, hydraulic analysis, stability analysis embung for rolling force, shear force, eccentricity, and bearing capacity of the soil. The results of the analysis are design flood Q50 = 13.715 m3 / sec, ogee crest type with R = 0.27 m and height 5 m, effective weir width 6.42 m, stilling basin USBR Type III. Calculation of weir stability analysis at normal water level conditions: stability of overturning (Sf = 2.618 ≥ 1.5), stability of shear (Sf = 5.321 ≥ 1.5), eccentricity (e = 0.234 ≤ 1.10), bearing capacity of the soil (σ1 = 27.079 ≤ 40 and σ2 = 17.574 ≤ 40). Stability values in flood water conditions: stability of overturning (Sf = 4.532 ≥ 1.5), stability of shear (Sf = 12.720 ≥ 1.5), eccentricity (e = -0.695 ≤1.10), bearing capacity of the soil (σ1 = 8.029 ≤ 40 and σ2 = 35.632 ≤ 40). Keywords: Lakuang Burai small dam, Flood Discharge, Ogee Type, Spillway Stability